Vague Language Explored
XIII, 251 p.
Keywords: Vague language ('bags of time', 'doing stuff', 'and all that') is an aspect of communicative competence of considerable social importance. This book examines its function. It spans genre analysis, critical discourse analysis, psycholinguistics and cross-cultural sociolinguistics, and suggests applications in TEFL and directions for future research.